A Indústria lítica do Gravettense Médio do Vau (Médio Vouga): apresentação de dados preliminares - Manzano, Carmen (2020)
This article focuses on data from the lower levels of the stratigraphic sequence identified at Vau, a Prehistoric site excavated in the scope of the Ribeiradio-Ermida dam project (middle Vouga). After a brief presentation of site location, stratigraphic sequence and excavation work, the main aspects of lithic technology are presented: raw materials sourcing, tool production, transformation and abandonment. Lithic refitting revealed additional technology data. Identification and excavation of this archaeological site provided new elements for the characterization of the Middle Gravettian phase, poorly known in Portuguese territory, as shown by the scarce parallels from Estremadura, Côa and Sabor river valleys.